Robotic-Assisted Lobectomy Favors Early Lung Recovery versus Limited Thoracotomy - Lacroix, Valérie; Kahn, David; Matte, Pascal; Pieters, Thierry; Noirhomme, Philippe; Poncelet, Alain; Steyaert, Arnaud (The Thoracic and Cardiovascular Surgeon, 2020)
Background Postoperative pulmonary recovery after lobectomy has showed early benefits for the video-assisted thoracoscopic surgery and sparing open techniques over nonsparing techniques. Robotic-assisted procedures offer benefits in term of clinical outcomes, but their advantages on pulmonary recovery and quality of life have not yet been distinctly prospectively studied.Methods Eighty-six patients undergoing lobectomy over a period of 29 months were prospectively studied for their pulmonary function recovery and pain score level during the in-hospital stay and at 1, 2, and 6 months. Quality of life was evaluated at 2 and 6 months. Forty-five patients were operated by posterolateral limited thoracotomy and 41 patients by robotic approach. The postoperative analgesia protocol differed for the two groups, being lighter for the robotic group.Results The pulmonary tests were not significantly different during the in-hospital stay. At 1 month, the forced expiratory volume in 1 second, forced vital capacity, vital capacity, and maximal expiratory pressure were significantly better for the robotic group (p = 0.05, 0.04, 0.05, and 0.02, respectively). There was no significant difference left at 2 and 6 months. Pain intensity was equivalent during the in-hospital stay but was significantly lower for the robotic group at 1 month (p = 0.02). At 2 and 6 months, pain and quality of life were comparable.Conclusion Robotic technique can offer similar pulmonary and pain recovery during the in-hospital stay with a lighter analgesia protocol. It clearly favors the early term recovery compared with the open limited technique. The objective and subjective functional recovery becomes equivalent at 2 and 6 months.
Keywords: lung cancer; pulmonary function; quality of life; robotic approach; postoperative pain